Designing a Web-Based Cashier Information System at Kedai Santai Cafe and Millennial Resto in Pabuaran - Sholahuddin, Muhammad Rifda; Auliana, Sigit; Purnama, Eris Dwi; Masyhuri, Maman; Safaatullah, Asep (Indonesian Research Journal on Education, 2024)
Today's technological development is developing very rapidly. The cashier information system in restaurants is very important to meet and facilitate the performance of cashiers. Therefore, the author conducted this study, Kedai Santai Cade and Resto Milenial. This study aims to determine what activities and problems occur when making payment transactions and aims to reduce the number of restaurant losses when calculating total customer losses. This study used observational analysis and interviews. The design method used is to use the Prototype Method as a foundation in designing a cashier information system that suits the needs of restaurants in managing payment transactions. The result of conducting this research is to design a web-based cashier information system at casual cafes and millennial restaurants to facilitate cashier performance and reduce losses incurred in the manual payment transaction process. This research can be concluded that technology must be developed. Technology can help process one's performance and activities such as the Cashier Information System which helps the performance of a cashier in making payment transactions with customers.